Genomic imprinting: A missing piece of the Multiple Sclerosis puzzle?. (October 2015) - Ruhrmann, Sabrina; Stridh, Pernilla; Kular, Lara; Jagodic, Maja
Abstract: Evidence for parent-of-origin effects in complex diseases such as Multiple Sclerosis (MS) strongly suggests a role for epigenetic mechanisms in their pathogenesis. In this review, we describe the importance of accounting for parent-of-origin when identifying new risk variants for complex diseases and discuss how genomic imprinting, one of the best-characterized epigenetic mechanisms causing parent-of-origin effects, may impact etiology of complex diseases. While the role of imprinted genes in growth and development is well established, the contribution and molecular mechanisms underlying the impact of genomic imprinting in immune functions and inflammatory diseases are still largely unknown. Here we discuss emerging roles of imprinted genes in the regulation of inflammatory responses with a particular focus on the Dlk1 cluster that has been implicated in etiology of experimental MS-like disease and Type 1 Diabetes. Moreover, we speculate on the potential wider impact of imprinting via the action of imprinted microRNAs, which are abundantly present in the Dlk1 locus and predicted to fine-tune important immune functions. Finally, we reflect on how unrelated imprinted genes or imprinted genes together with non-imprinted genes can interact in so-called imprinted gene networks (IGN) and suggest that IGNs could partly explain observed parent-of-origin effects in complex diseases. Unveiling the mechanisms of parent-of-origin effects is therefore likely to teach us not only about the etiology of complex diseases but also about the unknown roles of this fascinating phenomenon underlying uneven genetic contribution from our parents. This article is part of a Directed Issue entitled: Epigenetics dynamics in development and disease.